Micropropagation and Conservation of Aerides falcata Lindl. & Paxton by Artificial Seed Technique - หงส์ทองคำ, ดร.จตุพร; พรมวงศ์, รชยา; รัตนสุข, ผู้ช่วยศาสตราจารย์ ดร.สุรชัย (Journal of Food Health and Bioenvironmental Science, 2017)
Micropropagation and conservation of Aerides falcata Lindl. & Paxton by artificial seed technique is an alternative method for orchids germplasm preservation. The objectives of this study were to investigate the effect of NAA and BA on protocorms growth and to study the suitable of dehydration time and artificial seeds storage durations. The results showed that the highest average number of shoots, roots and plantlet height were 5.13 shoots/protocorm, 2.40 roots/shoot and 2.47 cm, respectively when protocorms were cultured on ND medium supplemented with 0.5 mg/l NAA and 5 mg/l BA. The study of dehydration time by air-drying in a laminar air flow cabinet for 0-6 h found that the optimum time of dehydration was 3 h. The water content and survival percentage of 3 h dehydrated artificial seeds were 28.95% and 98%. Dehydrated artificial seeds were stored at -20°C for 1-6 months. The results indicated that storage for 1 month showed the highest survival percentage of 100%.